GaS powder, GaS thin film electrode, preparation method of GaS powder and GaS thin film electrode, and photoelectric detector

High-crystallinity GaS powder and thin-film electrodes were prepared by the low-temperature deep eutectic solvent method, which solved the problems of low crystallinity of GaS materials and limited substrate selection, achieved efficient and stable optoelectronic performance, and promoted the application of flexible optoelectronic devices.

CN120736558AActive Publication Date: 2025-10-03XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511201999.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-10-03
Estimated Expiration
2045-08-26

AI Technical Summary

Technical Problem

The synthesized crystallinity of GaS materials is low, making it difficult to grow uniformly and controllably over a large area. The existing high-temperature preparation method has high energy consumption and limited substrate selection. The traditional low-temperature solution method has low crystallization quality, affecting the stability of optoelectronic performance and the repeatability of devices.

Method used

The low-temperature deep eutectic solvent method is used to prepare high-crystallinity GaS powder through multi-step heating and in-situ sulfurization. Subsequently, GaS thin film electrodes are formed at low temperature. High-quality thin film growth is achieved by using alcohol solvent dispersion and vacuum sealing annealing treatment.

Benefits of technology

GaS films with high crystallinity and good uniformity were prepared under low temperature conditions, which are suitable for flexible substrates, improve the response speed and stability of photodetectors, and promote the development of flexible optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120736558A_ABST
    Figure CN120736558A_ABST
Patent Text Reader

Abstract

The invention provides GaS powder, a GaS thin film electrode, a preparation method of the GaS thin film electrode and a photoelectric detector, and relates to the technical field of semiconductor materials. The preparation method of the GaS powder comprises the following steps: mixing choline chloride and urea, and performing stirring, vacuum cooling and water removal treatment to obtain a first intermediate product; in a protective atmosphere, adding GaCl3 into the first intermediate product for multiple times to obtain a second intermediate product; adding thiourea into the second intermediate product for multiple times to obtain a third intermediate product; adding NaBH4 into the third intermediate product to obtain a fourth intermediate product; the fourth intermediate product is subjected to annealing treatment, after annealing treatment, citric acid is adopted for cleaning, and GaS powder is obtained after centrifugal treatment. According to the invention, the crystallinity of the GaS material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of semiconductor materials, and in particular to a GaS powder, a GaS thin film electrode and a preparation method, and a photodetector. Background Art

[0002] GaS (gallium sulfide) is a typical III-VI layered two-dimensional semiconductor material with a direct band gap of about 2.5 eV (single layer) and an indirect band gap of about 2.3 eV (bulk phase). It exhibits strong light absorption ability in the ultraviolet to near-infrared band, and shows good carrier mobility, photoelectric response ability and environmental stability. Therefore, it has broad application prospects in photodetectors, field-effect transistors, photocatalysis and photoelectrochemical cells.

[0003] Currently, the synthesis of GaS materials generally suffers from low crystallinity and difficulty in achieving uniform and controllable growth over large areas. Providing an environmentally friendly and easy-to-operate GaS material synthesis process is of great significance for promoting its application in optoelectronic devices, especially flexible optoelectronic devices.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the Invention

[0005] The purpose of the present disclosure is to provide a GaS powder, a GaS thin film electrode and a preparation method, and a photodetector, thereby overcoming the problem of low crystallinity of synthesized GaS materials at least to a certain extent.

[0006] According to a first aspect of the present disclosure, a method for preparing GaS powder is provided, comprising: mixing choline chloride and urea, stirring and vacuum cooling to remove water to obtain a first intermediate product; adding GaCl3 to the first intermediate product in a protective atmosphere in multiple portions to obtain a second intermediate product; adding thiourea to the second intermediate product in multiple portions to obtain a third intermediate product; adding NaBH4 to the third intermediate product to obtain a fourth intermediate product; annealing the fourth intermediate product, washing it with citric acid after the annealing treatment, and obtaining GaS powder after centrifugation.

[0007] Optionally, choline chloride is mixed with urea, and after stirring and vacuum cooling and dehydration treatment, a first intermediate product is obtained, comprising: mixing 7-10 g of choline chloride with 10-15 g of urea, stirring at 80-90° C. for 30-60 min to obtain a molten salt product; and vacuum cooling and dehydration treatment of the molten salt product for 1-2 h to obtain the first intermediate product.

[0008] Optionally, GaCl3 is added to the first intermediate product in multiple times to obtain the second intermediate product, including: adding GaCl3 to the first intermediate product in 3 to 5 times to obtain the second intermediate product; wherein the total amount of GaCl3 added is 1 to 1.75 g, the interval time of each addition is 5 to 10 minutes, and in the process of obtaining the second intermediate product, stirring treatment is performed at 80 to 90°C and 300 to 500 rpm.

[0009] Optionally, thiourea is added to the second intermediate product in multiple times to obtain a third intermediate product, including: adding thiourea to the second intermediate product in 2 to 5 times to obtain the third intermediate product; wherein the total amount of thiourea added is 1 to 2 g, and in the process of obtaining the third intermediate product, stirring treatment is performed at 80 to 90°C.

[0010] Optionally, the amount of NaBH4 added to the third intermediate product is 0.1~0.3g.

[0011] Optionally, the fourth intermediate product is annealed, washed with citric acid after the annealing treatment, and centrifuged to obtain GaS powder, including: placing the fourth intermediate product in a vacuum tube furnace at 180~300℃ for 2~5h with a heating rate of 2~5℃ / min for annealing treatment; after the annealing treatment, washing with 0.01~0.05M citric acid, and centrifuging to obtain GaS powder.

[0012] According to a second aspect of the present disclosure, there is provided a GaS powder prepared by any of the above-mentioned methods for preparing GaS powder.

[0013] According to a third aspect of the present disclosure, a method for preparing a GaS thin film electrode is provided, comprising: dispersing GaS powder in an alcohol solvent and performing ultrasonication to obtain a dispersion; wherein the GaS powder is prepared using any of the above-mentioned methods for preparing GaS powder; spraying the dispersion onto a surface of a substrate to form a precursor electrode; dripping an (NH4)2S solution onto the surface of the precursor electrode, and performing an annealing treatment after vacuum sealing to obtain a GaS thin film electrode.

[0014] According to a fourth aspect of the present disclosure, a GaS thin film electrode is provided, which is prepared using the above-mentioned method for preparing a GaS thin film electrode.

[0015] According to a fifth aspect of the present disclosure, a photodetector is provided, comprising a GaS thin film electrode, wherein the GaS thin film electrode is prepared using the above-mentioned method for preparing the GaS thin film electrode.

[0016] In the exemplary embodiments of the present disclosure, a solution-based preparation method is used to produce GaS powder, resulting in excellent crystallinity, simple operation, environmental friendliness, and low cost. Furthermore, through the selection of raw materials and control of process steps, such as the addition of thiourea in multiple steps, the present disclosure can further improve the crystallization quality of GaS, helping to promote the application of GaS materials in fields such as photodetectors.

[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and those skilled in the art can derive other drawings based on these drawings without inventive effort.

[0019] Figure 1 The diagram schematically shows the mechanism of preparing GaS material according to an embodiment of the present disclosure.

[0020] Figure 2 A flow chart schematically shows a method for preparing GaS powder according to an exemplary embodiment of the present disclosure.

[0021] Figure 3 A flow chart schematically illustrates a method for preparing a GaS thin film electrode according to an exemplary embodiment of the present disclosure.

[0022] Figure 4 The XRD (X-Ray Diffraction) patterns of the GaS material at different annealing temperatures according to the embodiment of the present disclosure are schematically shown.

[0023] Figure 5 The schematic diagram of the ultraviolet-visible light diffuse reflection of the GaS material according to the embodiment of the present disclosure is schematically shown.

[0024] Figure 6 The following schematically shows SEM (Scanning Electron Microscope) images of the surface of the GaS thin film electrode according to an embodiment of the present disclosure, wherein Figure A is a microscopic morphology image at a scale of 10 μm, and Figure B is a microscopic morphology image at a scale of 5 μm.

[0025] Figure 7 The photoelectric response curves of the GaS material at different annealing temperatures according to the embodiment of the present disclosure are schematically shown.

[0026] Figure 8The IV test curve of the GaS material according to the embodiment of the present disclosure is schematically shown.

[0027] Figure 9 The optical response curves of the GaS material of the embodiment of the present disclosure under different optical powers are schematically shown.

[0028] Figure 10 A schematic diagram of a photodetector including a GaS thin film electrode according to an embodiment of the present disclosure is shown.

[0029] Figure 11 A schematic diagram showing the response speed of the photodetector of Example 1 of the present disclosure to 380 nm laser light is shown.

[0030] Figure 12 A schematic diagram showing the response speed of the photodetector of Example 2 of the present disclosure to 380 nm laser light is shown.

[0031] Figure 13 A schematic diagram showing the response speed of the photodetector of Example 3 of the present disclosure to 380 nm laser light is shown. DETAILED DESCRIPTION

[0032] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that the present disclosure will be more comprehensive and complete and will fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or that other methods, processes, steps, etc. may be employed. In other cases, well-known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0033] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and their repeated description will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all steps. For example, some steps can be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to actual circumstances. In addition, all the terms "first", "second", "third", "fourth", etc. below are only for the purpose of distinction and should not be used as limitations of the content of this disclosure.

[0034] Currently, the main methods for preparing GaS include mechanical exfoliation, chemical vapor deposition (CVD), and physical vapor transport (PVT). CVD is widely used due to its ability to controllably prepare large-area films. However, it typically requires high temperatures exceeding 900°C, resulting in high energy consumption and equipment costs. Furthermore, it is incompatible with the low-temperature preparation requirements of flexible substrates or back-end integrated circuit processes, severely limiting its application in flexible electronics and low-temperature devices.

[0035] In contrast, the solution method offers advantages such as low cost, simple process, and ease of large-area film formation, making it considered a potential alternative route. However, GaS thin films prepared by conventional solution methods generally suffer from low crystallinity, small grain size, poor film uniformity, and organic residues. These issues lead to low carrier mobility, high dark current, and slow response speed, severely impacting the stability of the optoelectronic performance and the reproducibility of the device. Achieving the controlled growth of highly crystalline, large-area uniform GaS thin films at relatively low temperatures (e.g., below 300°C) remains a current technical challenge. Therefore, developing a new method for the efficient preparation of highly crystalline, uniform GaS nanomaterials or thin films at relatively low temperatures, overcoming the dual bottlenecks of poor compatibility of existing high-temperature preparation methods and low crystal quality of traditional low-temperature solution methods, and developing an environmentally friendly, easy-to-operate, and applicable low-temperature synthesis process for a variety of substrates, is of great significance for promoting the practical application of GaS-based optoelectronic devices.

[0036] In view of this, the embodiments of the present disclosure provide a new method for preparing GaS powder.

[0037] Figure 1 The schematic diagram shows the mechanism of preparing GaS material by low temperature method using low temperature deep eutectic solvent according to the embodiment of the present disclosure. Figure 1 Choline chloride is mixed with urea, and GaCl3 and thiourea are added multiple times. Under the action of dual control agents, multi-step heating is carried out through the pre-nucleation stage, nucleation-growth stage and growth stage to achieve in-situ sulfurization and obtain high-crystallinity gallium sulfide.

[0038] Figure 2 The flowchart of the method for preparing GaS powder according to an exemplary embodiment of the present disclosure is schematically shown. Figure 2 The method for preparing GaS powder according to the embodiment of the present disclosure may include the following steps: S20. Choline chloride and urea are mixed, stirred, and vacuum-cooled to remove water, thereby obtaining a first intermediate product.

[0039] First, 7-10 g of choline chloride and 10-15 g of urea can be mixed and stirred at 80-90° C. for 30-60 minutes to obtain a molten salt product. Next, the molten salt product can be vacuum cooled and dehydrated for 1-2 hours to obtain a first intermediate product.

[0040] For example, 7g of choline chloride and 10g of urea are weighed and added to a 50mL glass reagent bottle. The mixture is stirred at 80-90°C for 30-60 minutes until a completely transparent molten salt is formed. The resulting transparent molten salt is then cooled to room temperature under vacuum conditions and stored under vacuum for 1-2 hours until the water in the solution is completely evaporated, thereby obtaining the first intermediate product.

[0041] S22. Under a protective atmosphere, adding GaCl3 to the first intermediate product in multiple portions to obtain a second intermediate product.

[0042] The embodiment of the present disclosure does not limit the type of protective atmosphere, such as nitrogen or inert gas.

[0043] Specifically, GaCl₃ can be added to the first intermediate product in 3-5 additions to obtain the second intermediate product. The total amount of GaCl₃ added is 1-1.75 g, with each addition interval lasting 5-10 minutes. During the process of obtaining the second intermediate product, stirring is performed at 80-90°C and 300-500 rpm. The amount of GaCl₃ added each time can be the same or different.

[0044] For example, the first intermediate product obtained in step S20 is heated to 80-90° C., and 1.75 g of GaCl 3 is added three times under nitrogen protection, with a stirring speed of 500 rpm and a time interval of 10 minutes between each addition of GaCl 3.

[0045] S24. Add thiourea to the second intermediate product in multiple steps to obtain a third intermediate product.

[0046] Specifically, thiourea is added to the second intermediate product in 2 to 5 portions to obtain the third intermediate product, wherein the total amount of thiourea added is 1 to 2 g, and the third intermediate product is stirred at 80 to 90° C. during the process of obtaining the third intermediate product.

[0047] S26. NaBH4 is added to the third intermediate product to obtain a fourth intermediate product.

[0048] Specifically, 0.1-0.3 g of NaBH 4 is added to the third intermediate product to inhibit the formation of oxides, so as to obtain a fourth intermediate product.

[0049] S28. Annealing the fourth intermediate product. After annealing, washing with citric acid and centrifuging to obtain GaS powder.

[0050] Specifically, the fourth intermediate product is annealed in a vacuum tube furnace at 180-300°C for 2-5 hours at a heating rate of 2-5°C / min. After annealing, the product is washed with 0.01-0.05M citric acid to remove residual organic matter and centrifuged to obtain GaS powder. The centrifuge speed is 3000-4000 rpm.

[0051] Furthermore, an embodiment of the present disclosure also provides a GaS powder, which is prepared using the above-mentioned method for preparing GaS powder.

[0052] Based on the aforementioned GaS solution, high-crystalline quality GaS materials can be synthesized at temperatures below 300°C. This allows, for example, flexible substrate materials (such as PET and polyimide) to have low melting points. The low-temperature synthesis of high-quality GaS materials is of significant value for applications such as the integration of flexible semiconductor devices, and can promote the development of flexible optoelectronic applications such as wearable devices and wearable fabrics.

[0053] Figure 3 The flowchart of the method for preparing the GaS thin film electrode according to the exemplary embodiment of the present disclosure is schematically shown. Figure 3 The method for preparing the GaS thin film electrode according to the embodiment of the present disclosure comprises the following steps: S30. Dispersing GaS powder in an alcohol solvent and performing ultrasonication to obtain a dispersion.

[0054] The GaS powder used in this step is the GaS powder prepared by the above-mentioned method for preparing GaS powder. In addition, the present disclosure does not limit the type of alcohol solvent, for example, it can be one of ethanol, methanol, and isopropanol.

[0055] Specifically, 0.05-0.15 g of GaS powder can be dispersed in 10 mL of an alcohol solvent and ultrasonicated for 30-40 minutes.

[0056] S32. Spraying the dispersion onto a substrate surface to form a precursor electrode.

[0057] The substrate used in the present disclosure may be a substrate selected from sapphire, ITO, and n-Si, and the size is, for example, 10×20×0.35 mm.

[0058] S34. Add (NH4)2S solution to the surface of the precursor electrode, seal the tube in vacuum, and then perform annealing to obtain a GaS thin film electrode.

[0059] Specifically, 10-30 μL of (NH₄)₂S solution was dripped onto the surface of the precursor electrode as a S source supplement. The electrode was then vacuum-sealed in a tube furnace and annealed at 250-300°C for 1-3 hours, with the heating rate controlled at 2-5°C / min. After cooling to room temperature, a GaS thin film electrode was obtained.

[0060] Furthermore, the present disclosure also provides a GaS thin film electrode, which is prepared using the above-mentioned method for preparing a GaS thin film electrode. The GaS thin film electrode has an optimal response speed of 7 μs under 380 nm light.

[0061] Furthermore, the embodiment of the present disclosure also provides a photodetector, which includes the above-mentioned GaS thin film electrode. The device has a power of 0~100mW / cm 2 The photocurrent response is linear within the optical power range.

[0062] For example, the above-mentioned GaS thin film electrode can be integrated with a packaging structure to form an ultraviolet detector, a transparent electrode integrated detector or a high-frequency detector.

[0063] The exemplary solution of the present disclosure is described below through Example 1, which may include the following steps: Step 1: Weigh 7.4 g of choline chloride and 10 g of urea, add them to a 50 mL glass reagent bottle, and stir at 85 °C for 40 min until a completely transparent molten salt is formed.

[0064] Step 2: Cool the obtained transparent molten salt to room temperature under vacuum conditions and store it under vacuum for 1 hour until the water in the solution is completely evaporated.

[0065] Step 3: The product obtained in step 2 was heated to 80°C again, and then 1.75 g of GaCl3 was added three times under nitrogen protection, with a stirring speed of 300 rpm and a time interval of 5 minutes for each addition of GaCl3.

[0066] Step 4: Add 2 g of thiourea twice to the product obtained in step 3, and maintain the temperature at 80°C during the entire stirring process.

[0067] Step 5: 0.2 g of NaBH4 was added to the product obtained in step 4 to suppress the formation of oxides.

[0068] Step 6: The product obtained in step 5 was cooled to room temperature, and then placed in a glass ark and kept at 250°C in a vacuum tube furnace for 3 hours. The heating rate of the whole process was controlled at 2°C / min.

[0069] Step 7: The product obtained in step 6 was washed with 0.01 M citric acid to remove organic residues, then rinsed with clean water and centrifuged at 4000 rpm to obtain GaS powder.

[0070] Figure 4 The XRD patterns of GaS materials at different annealing temperatures in the embodiment of the present disclosure are schematically shown. That is, in addition to the above annealing treatment at 250°C, annealing treatments at 180°C and 300°C were also performed. Figure 4 As shown, it can be seen that compared with 180℃ and 300℃, the crystallinity is best after annealing at 250℃.

[0071] Figure 5 The schematic diagram of the diffuse reflection of ultraviolet and visible light of the GaS material of the embodiment of the present disclosure is shown schematically. Figure 5 The results shown in FIG. 4 show that the band gap of the GaS material prepared in Example 1 of the present disclosure is 2.5 eV.

[0072] Step 8: Weigh 0.1 g of the GaS powder obtained in step 7, disperse it in 10 mL of ethanol solution, ultrasonically disperse it for 30 minutes, and then spray it on the surface of a 10×20×0.35 mm sapphire substrate to prepare a GaS precursor electrode.

[0073] Step 9: Add 10 μL of (NH₄)₂S solution to the surface of the GaS precursor electrode prepared in Step 8 as a sulfur source supplement. Subsequently, the electrode was vacuum-sealed and annealed in a tube furnace at 250°C for 1 hour at a heating rate of 2°C / min. After cooling to room temperature, a GaS thin film electrode was obtained.

[0074] Figure 6 The SEM images of the surface of the GaS thin film electrode of the embodiment of the present disclosure are schematically shown, wherein Figure A is a microscopic morphology image at a scale of 10 μm, and Figure B is a microscopic morphology image at a scale of 5 μm.

[0075] The optical properties of the prepared GaS / sapphire substrate electrode were characterized, and it can be seen that the GaS / sapphire electrode has good photoelectric detection performance.

[0076] Figure 7 The photoelectric response curves of GaS (380 nm) materials at different annealing temperatures according to the embodiment of the present disclosure are schematically shown. Figure 7 It can be seen that the prepared GaS semiconductor film has the characteristics of n-type semiconductor. The photocurrent is the largest when the annealing temperature is 250℃. Therefore, this temperature is the optimal sintering temperature.

[0077] Figure 8The schematic diagram shows the embodiment of the present disclosure at 5mW / cm 2 IV test curve of GaS material under light excitation. Figure 8 It can be seen that the current of the GaS film prepared in Example 1 of the present disclosure changes linearly with the increase of voltage, and this change has important advantages in the field of sensors.

[0078] Figure 9 The light response curves of the GaS material of the embodiment of the present disclosure under different light powers are schematically shown. Figure 9 , it can be seen that under different light intensities, GaS semiconductor films have good photoresponse characteristics.

[0079] In addition, the above-mentioned GaS / sapphire electrodes are packaged to prepare photoelectric sensors, such as Figure 10 As shown. And test the sensitivity of the sensor, refer to Figure 11 It can be seen that the photoelectric sensor prepared in Example 1 of the present disclosure has a response speed of 7 μs to 380 nm ultraviolet light, and has excellent performance.

[0080] The following describes an exemplary embodiment of the present disclosure through Example 2, which may include the following steps: Step 1: Weigh 7.4 g of choline chloride and 10 g of urea, add them to a 50 mL glass reagent bottle, and stir at 85 °C for 40 min until a completely transparent molten salt is formed.

[0081] Step 2: Cool the obtained transparent molten salt to room temperature under vacuum conditions and store it under vacuum for 1.5 hours until the water in the solution is completely evaporated.

[0082] Step 3: The product obtained in step 2 was heated to 80°C again, and then 1.75 g of GaCl3 was added three times under nitrogen protection, with a stirring speed of 400 rpm and a time interval of 7 minutes for each addition of GaCl3.

[0083] Step 4: Add 2 g of thiourea twice to the product obtained in step 3, and maintain the temperature at 85°C during the entire stirring process.

[0084] Step 5: Add 0.1 g of NaBH4 to the product obtained in step 4 to suppress the formation of oxides.

[0085] Step 6: The product obtained in step 5 was cooled to room temperature, and then placed in a glass ark and kept at 250°C in a vacuum tube furnace for 3 hours. The heating rate of the whole process was controlled at 2°C / min.

[0086] Step 7: The product obtained in step 6 was washed with 0.03 M citric acid to remove organic residues, then rinsed with clean water and centrifuged at 4000 rpm to obtain GaS powder.

[0087] Step 8: Weigh 0.1 g of the GaS powder obtained in step 7, disperse it in 10 mL of ethanol solution, ultrasonically disperse it for 30 minutes, and then spray it on the surface of a 10×20×0.35 mm ITO substrate to prepare a GaS precursor electrode.

[0088] Step 9: Add 10 μL of (NH₄)₂S solution to the surface of the GaS precursor electrode prepared in Step 8 as a sulfur source supplement. Subsequently, the electrode was vacuum-sealed and annealed in a tube furnace at 280°C for 1 hour at a heating rate of 2°C / min. After cooling to room temperature, a GaS thin film electrode was obtained.

[0089] Subsequently, the optical characteristics of the GaS thin film electrode can be characterized and a photoelectric sensor can be prepared using the GaS thin film electrode.

[0090] The GaS thin film electrode has n-type semiconductor characteristics. The sensitivity of the photoelectric sensor prepared based on the GaS thin film electrode was tested. Figure 12 It can be seen that the response speed of the photoelectric sensor prepared in Example 2 of the present disclosure to 380nm ultraviolet light is 12μs.

[0091] The following describes an exemplary solution of the present disclosure through Example 3, which may include the following steps: Step 1: Weigh 7.4 g of choline chloride and 10 g of urea, add them to a 50 mL glass reagent bottle, and stir at 90 ° C for 60 min until a completely transparent molten salt is formed.

[0092] Step 2: Cool the obtained transparent molten salt to room temperature under vacuum conditions and store it under vacuum for 2 hours until the water in the solution is completely evaporated.

[0093] Step 3: The product obtained in step 2 was heated to 90° C. again, and then 1.75 g of GaCl 3 was added three times under nitrogen protection, with a stirring speed of 400 rpm and a time interval of 10 min for each addition of GaCl 3.

[0094] Step 4: Add 2 g of thiourea twice to the product obtained in step 3, and maintain the temperature at 90°C during the entire stirring process.

[0095] Step 5: 0.3 g of NaBH4 was added to the product obtained in step 4 to suppress the formation of oxides.

[0096] Step 6: The product obtained in step 5 was cooled to room temperature, and then placed in a glass ark and kept at 250°C in a vacuum tube furnace for 3 hours. The heating rate of the whole process was controlled at 2°C / min.

[0097] Step 7: The product obtained in step 6 was washed with 0.05 M citric acid to remove organic residues, then rinsed with clean water and centrifuged at 4000 rpm to obtain GaS powder.

[0098] Step 8: Weigh 0.1 g of the GaS powder obtained in step 7, disperse it in 10 mL of ethanol solution, ultrasonically disperse it for 30 minutes, and then spray it on the surface of a 10×20×0.35 mm n-Si substrate to prepare a GaS precursor electrode.

[0099] Step 9: Add 10 μL of (NH₄)₂S solution to the surface of the GaS precursor electrode prepared in Step 8 as a sulfur source supplement. Subsequently, the electrode was vacuum-sealed and annealed in a tube furnace at 300°C for 1 hour at a heating rate of 2°C / min. After cooling to room temperature, a GaS thin film electrode was obtained.

[0100] Subsequently, the optical characteristics of the GaS thin film electrode can be characterized and a photoelectric sensor can be prepared using the GaS thin film electrode.

[0101] The GaS thin film electrode has n-type semiconductor characteristics. The sensitivity of the photoelectric sensor prepared based on the GaS thin film electrode was tested. Figure 13 It can be seen that the response speed of the photoelectric sensor prepared in Example 3 of the present disclosure to 380nm ultraviolet light is 17μs.

[0102] The disclosed embodiments solve the problem of high energy consumption and limited substrate selection caused by the need for high-temperature treatment in the preparation of existing GaS materials through the above-mentioned scheme, while breaking through the limitations of low crystallinity, poor film uniformity and unstable photoelectric performance that are prone to occur during low-temperature synthesis. The use of deep eutectic solvents as reaction media enables the low-temperature controllable growth of GaS nanostructures. The obtained GaS material has good crystallization quality and film uniformity, and is suitable for the construction of photodetectors, field-effect transistors and catalytic devices. The photodetector device prepared based on this material exhibits excellent response speed and stability, providing a key technical path for the development of low-temperature compatible photoelectric devices.

[0103] It should be noted that although the steps of the method of the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all steps must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps.

[0104] Furthermore, the figures above are merely illustrative of the processes included in the methods according to exemplary embodiments of the present disclosure and are not intended to be limiting. It is readily understood that the processes illustrated in the figures above do not indicate or limit the temporal order of these processes. Furthermore, it is readily understood that these processes may be executed synchronously or asynchronously, for example, in multiple modules.

[0105] Other embodiments of the present disclosure will readily occur to those skilled in the art after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered as exemplary only, with the true scope and spirit of the present disclosure being indicated by the claims.

[0106] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes can be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing GaS powder, characterized in that: include: The choline chloride and urea are mixed, stirred, cooled under vacuum and dehydrated to obtain a first intermediate product; Under a protective atmosphere, adding GaCl3 to the first intermediate product in multiple times to obtain a second intermediate product; adding thiourea to the second intermediate product in multiple portions to obtain a third intermediate product; adding NaBH4 to the third intermediate product to obtain a fourth intermediate product; The fourth intermediate product is annealed, washed with citric acid, and centrifuged to obtain GaS powder.

2. The preparation method according to claim 1, characterized in that Choline chloride and urea are mixed, stirred, cooled under vacuum and dehydrated to obtain a first intermediate product, including: Mix 7-10 g of choline chloride with 10-15 g of urea and stir at 80-90°C for 30-60 min to obtain a molten salt product; The molten salt product is subjected to a vacuum cooling and water removal treatment for 1 to 2 hours to obtain a first intermediate product.

3. The preparation method according to claim 1, characterized in that Adding GaCl3 to the first intermediate product in multiple steps to obtain a second intermediate product, comprising: adding GaCl3 to the first intermediate product in 3 to 5 portions to obtain a second intermediate product; The total amount of GaCl3 added is 1-1.75 g, the interval between each addition is 5-10 min, and in the process of obtaining the second intermediate product, stirring treatment is performed at 80-90° C. and 300-500 rpm.

4. The preparation method according to claim 1 or 3, characterized in that Adding thiourea to the second intermediate product in multiple portions to obtain a third intermediate product, comprising: adding thiourea to the second intermediate product in 2 to 5 portions to obtain a third intermediate product; The total amount of thiourea added is 1-2 g, and the mixture is stirred at 80-90° C. during the process of obtaining the third intermediate product.

5. The preparation method according to claim 1, characterized in that The amount of NaBH4 added to the third intermediate product is 0.1~0.3g.

6. The preparation method according to claim 1, characterized in that The fourth intermediate product is annealed, washed with citric acid, and centrifuged to obtain GaS powder, including: The fourth intermediate product is placed in a vacuum tube furnace at 180-300° C. for 2-5 hours at a heating rate of 2-5° C. / min for annealing; After annealing, the product was washed with 0.01-0.05 M citric acid and centrifuged to obtain GaS powder.

7. A GaS powder, characterized in that: The GaS powder is prepared by the method for preparing the GaS powder according to any one of claims 1 to 6.

8. A method for preparing a GaS thin film electrode, characterized in that: include: Dispersing GaS powder in an alcohol solvent and performing ultrasonication to obtain a dispersion; wherein the GaS powder is prepared by the method for preparing GaS powder according to any one of claims 1 to 6; spraying the dispersion onto a substrate surface to form a precursor electrode; A (NH4)2S solution is dripped onto the surface of the precursor electrode, and the precursor electrode is sealed in a vacuum tube and then annealed to obtain a GaS thin film electrode.

9. A GaS thin film electrode, characterized in that: The GaS thin film electrode is prepared using the method for preparing the GaS thin film electrode as claimed in claim 8.

10. A photoelectric detector, characterized in that: It comprises a GaS thin film electrode, which is prepared by the preparation method of the GaS thin film electrode as claimed in claim 8.

Citation Information

Patent Citations

  • Sulfide annealing copper indium gallium sulfur solar cell thin film material preparation method after double-potential step method electrodeposition

    CN105226117A

  • Solution method for preparing high-efficiency CIS and CIGS thin-film solar cell

    CN109817735A

  • Preparation method of antimony selenide thin-film solar cell

    CN112201725A

  • Method for preparing Se-Sb semiconductor film through electro-deposition in deep eutectic solvent

    CN118932447A

  • Solution-based process for making inorganic materials

    US20100261304A1